Miradi Measures Dashboard Demo - Salzer, D (2013)
Live demonstration (view in HD) of a new online measures dashboard site (http://miradi.sitkatech.com) that allows users of the Miradi Adaptive Management software (http://miradi.org) to share the progress they are making towards achieving their desired results

Complexity-Aware Monitoring - Britt, Heather; Patsalides, Melissa (USAID's Learning, Evaluation, and Research Office, 2013)